On the bright side, I'm now the girlfriend of a Sex God : further confessions of Georgia Nicolson - Rennison, Louise (New York, NY : HarperTempest, 2002)
Fourteen-year-old Georgia continues her diary in which she records her misadventures trying to reclaim the attention of seventeen-year-old Robbie, while coping with her friends, family, and dog-like cat Angus at the same time.
Previously published: New York : HarperCollins, 2001.
Sequel: Knocked out by my nunga-nungas.
Sequel to: Angus, thongs, and full-frontal snogging.
Keywords: Dating (Social customs) -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Diaries -- Juvenile fiction; Family -- England -- Juvenile fiction; Humorous stories; England -- Juvenile fiction